Problem of professional preparation of teachers of higher school to pedagogical activity in the conditions of master’s degree education in scientific researches - Княжева, Ірина (Educational Dimension, 2015)
Knyazheva I. A. Problem of professional preparation of teachers of higher school to pedagogical activity in the conditions of master’s degree education in scientific researches. In the article the analysis of problem of professional preparation of teachers of higher school to pedagogical activity in the conditions of master’s degree education in a theory and practice of higher education is conducted. The special attention is spared illumination of issues of professional preparation of future specialists in area of preschool education, including pedagogical disciplines teachers of speciality «pre-school education».